Letting go or giving up? The influence of self-transcendence meaning of life on goal adjustment in high action crisis - Hu, Xinyi; Zhang, Heyi; Geng, Meifang (Frontiers in Psychology, 2023)
When individuals pursuing personal goals encounter setbacks and failures, they often fall into a conflict between disengaging from and striving toward the goal, defined as an action crisis. The present study investigated the influence and mechanism of self-transcendence meaning of life (STML) on goal disengagement and reengagement during a high versus a low action crisis. Study 1 included situations with different action crises. In Study 1, participants with high STML exhibited significantly higher goal disengagement and reengagement during high action crisis compared with low action crisis. Study 2 replicated the findings in Study 1 using participants’ personal goals by questionnaires, and further exhibited that action crisis had negative effect on self-efficacy for participants with low STML, and this process subsequently reduced goal adjustment. Interestingly, no mediation effect of self-efficacy was found between action crisis and goal adjustment among participants with high STML. Findings from the present study suggest that releasing obsessions and adopting a dialectical relationship between success and failure may help individuals in high action-crisis situations, and self-efficacy may provide flexibility and autonomy.